Pembuatan Peta Citra Desa Ngargosari Kecamatan Samigaluh Kabupaten Kulon Progo - Taufik Hery Purwanto; Karen Slamet Hardjo; Agung Jauhari; Rendy Putra Maretika (Jurnal Pengabdian dan Pengembangan Masyarakat, 2019)
Availability and understanding about the importance of spatial data, especially Village Maps, forrural communities are still minimum. Ngargosari Village, a village in Samigaluh District, KulonProgo Regency, was almost never used spatial data or maps to support the development.Whereas, UU 6 of 2014 concerning Villages states that Village Maps are the basis of informationand support systems in policy making. Village Map is a basic thematic map that containselements and information such as regional boundaries, roads/ infrastructure, topography,waters, facilities, and land use, which were presented in image maps, maps of facilities andinfrastructure, as well as land cover maps and land use (Perka BIG No. 3 in 2016 concerningTechnical Specifications for Presentation of Village Maps). Therefore, this community serviceaims to emphasize an understanding of the importance of Geospatial Information. Thecommunity is involved in making Village Maps through participatory mapping. The methods thatwere used are a remote sensing approach, field survey, and Focus Group Discussion (FGD)involving the Village Head, Village Officials, Hamlet Heads and Community Leaders. The resultsof this service are in the form of a map of the image of the Ngargosari Village which containsinformations about the boundaries of the village administration and hamlets, and also regionalfacilities and infrastructure.